Land use efficiency as consequence of virtual activities during Covid-19 pandemic - Puspita, Iredo Bettie (American Institute of Physics Inc., 2023)
The Covid-19 pandemic has urged people to adjust their way of life. Due to the Covid-19 pandemic, people must practice physical distancing, avoid the crowds, and minimize their mobility. The situation forces them to carry out various productive activities online or virtually by utilizing the information and communication technology. Online learning, working from home, online shopping, and even using online health consultation services are among the unavoidable activities which appear and are experienced by many during the Covid-19 pandemic. The shift in people's behavior towards virtual or online activities will undoubtedly encourage land-use efficiency. Specifically, this study explored the influence of virtual or online activities on the efficiency of physical space, by measuring the land-use efficiency based on the combinations of three measurements, namely: the ratio of various activities, the ratio of online multi-activities actors, and the ratio of space area. The analysis employed the data obtained from 436 respondents who carried out virtual or online activities in Semarang City and Yogyakarta City. The data was collected through the random distribution of spatial-based online questionnaires. The results found that the appearance and implementation of virtual or online activities has led to a pattern of multiple activities on one type of land use, thus giving rise to the multipurpose characteristics in land use patterns. During the Covid-19 pandemic, residential areas became the areas which have experienced an increase in the intensity and variety of activities, indicating land-use efficiency. Residential areas which have the main function as living quarters are currently developing the spaces for various other purposes, such as working, shopping, learning, and the other productive activities. © 2023 Author(s).